Barriers to reading English texts in schools of Rakwadu Circuit in Mopani District, Limpopo Province - Modipane, Makgomo Christina (My University, 2018)
This study investigated barriers to the reading of English texts in the rural schools of the Rakwadu Circuit in Mopani District, Limpopo Province. This problem is not only in the said Circuit, it is a world-wide challenge. The research was undertaken in three public secondary schools, with focus on the Grade 9 learners of the said Circuit. Data were collected through audio-taped interviews and observation of learners while reading prescribed texts. It was found that most educators and learners agree that there are barriers to the reading of English texts. The following factors were identified as barriers, namely: lack of libraries, non-parental involvement and insufficient learner-support materials, as well as lack of guided reading books. The study recommends that governmental officials should consider building libraries even in the rural schools and communities. The schools should have a parental involvement policy in which parents are encouraged to take part in the education of their children. The Department of Education should provide sufficient learner-support materials in schools to enhance learners’ reading ability. Educators are to be provided with guided reading materials that will enable them to implement Guided Reading approach. Curriculum advisors should train teachers on how to teach reading.
Thesis (M.Ed.) -- University of Limpopo, 2018
Keywords: Reading; English First Additional Language (EFAL); Curriculum; Active learning.; Children-Books and reading--English-speaking countries.